Control algorithm for G2V/V2G operation under unbalanced grid condition - Sharma, Sohit; Aware, Mohan; Bhowate, Apekshit (2017 7th International Conference on Power Systems (ICPS), 2017)
This paper presents the critical side of the control of grid connected electric vehicles. Grid to vehicle (G2V) and vehicle to grid (V2G) are two operating modes that are possible with electric vehicles. In the conventional control algorithm with single reference frame controller when the grid voltages are unbalanced, double frequency oscillations are appeared in grid currents in dq synchronous reference frame and also having higher THD. For solving this problem, dual reference frame controller is developed with notch filters. It removes the double frequency oscillations from dq sequence current but is not accurately detected. In the proposed algorithm, a decoupled network is used to extract sequence components of grid voltage and current. Proposed algorithm works on the principle of double synchronous reference frame theory which accurately maintain the sequence components as dc quantity and THD as per IEEE International Grid Standards. The control algorithm is explained with detailed block diagram and its effectiveness is validated by simulation results.